Space-time Estimate to Heat Equation (Journal of Partial Differential Equations, 2007)
In this article, we prove the Strichartz type estimate for the solutions of linear heat equation with initial data in Hardy space H¹(R^d). As an application, we obtain the full space-time estimate to the solutions of heat equation with initial data in L^p(R^d) for 1 ‹ p ‹ ∞.